Interesting case report on Chiari network - Kumar, Dheeraj; Singh, Gajram; Singh, Mahendra; Singh, Jyotsana (International Journal Of Community Medicine And Public Health, 2024)
The Chiari network is a congenital remnant that is typically found in the right atrium and is generally not associated with significant pathophysiological implications. Usually, this is detected on general routine health checkup screening or casual examination. But, occasionally in certain cases, it is possible for this condition to results in diagnostic ambiguity when assessing right atrial disorders. Additionally, it has potential to contribute to the development of thromboembolism by inducing flow blockage. The Chiari network can be accurately diagnosed by echocardiography. This network appear as a highly mobile, highly reflectant echo target at many regions in the right atrium during transthoracic and transesophageal echocardiography. In this study, we provide a case involving an 18 year old male students studying cardiac technology who was diagnosed incidentally during echocardiography practical classes with Chiari network, mild TR and mild PR. The value and precision of echocardiography are becoming more widely recognized and being used more frequently. The potential for finding normal anatomical variations and their potential incorrect interpretation as pathological states coincides with the wider implementation of this imaging method.